A common metabolomic signature is observed upon inoculation of rice roots with various rhizobacteria. Issue 2 (22nd May 2019) - Valette, Marine; Rey, Marjolaine; Gerin, Florence; Comte, Gilles; Wisniewski‐Dyé, Florence
Abstract: Plant growth‐promoting rhizobacteria (PGPR), whose growth is stimulated by root exudates, are able to improve plant growth and health. Among those, bacteria of the genus Azospirillum were shown to affect root secondary metabolite content in rice and maize, sometimes without visible effects on root architecture. Transcriptomic studies also revealed that expression of several genes involved in stress and plant defense was affected, albeit with fewer genes when a strain was inoculated onto its original host cultivar. Here, we investigated, via a metabolic profiling approach, whether rice roots responded differently and with gradual intensity to various PGPR, isolated from rice or not. A common metabolomic signature of nine compounds was highlighted, with the reduced accumulation of three alkylresorcinols and increased accumulation of two hydroxycinnamic acid amides (HCAA), identified as N ‐ p ‐coumaroylputrescine and N ‐feruloylputrescine. This was accompanied by the increased transcription of two genes involved in the N ‐feruloylputrescine biosynthetic pathway. Interestingly, exposure to a rice bacterial pathogen triggered a reduced accumulation of these HCAA in roots, a result contrasting with previous reports of increased HCAA content in leaves upon pathogen infection. Accumulation of HCAA, that are potential antimicrobial compounds, might be considered as a primary reaction of plant to bacterial perception. Abstract : Rhizobacteria (i.e. bacteria interacting with plant roots) can modify the accumulation of plant secondary metabolites. Here, a common metabolic signature, mainly involving hydroxycinnamic acid derivatives, was highlighted in rice roots inoculated with various rhizobacteria which belong to different species and genera, and were isolated from various plants.